The private letter discovered in Nikonionv - Głuszek, Inga (Acta Archaeologica Lodziensia, 2021)
The aim of this article is to present the two ostraca found in Greek polis of Nikonion on the northern shore of the Black Sea. The ostraca were found in 2007 and 2010 and they are the remains of a private letter which was send by one of the inhabitants of the polis to his relatives. Both fragments were translated and published in Zeitschrift für Papyrologie und Epigraphik. This article presents further interpretation in the context of the social, economic and agricultural conditions of the Greek poleis of the northern Black Sea coast. The letter has preserved some information about the system and conditions of the trade, and also delivered some figures about monetary system in use at Nikonion. Special attention has been paid to all information from the text which highlight the problem of the connections of the polis with smaller Greek settlements which constituted the chora of the city. The text of the letter shows how intensive and complex the economy of that polis was during the 4th century BC, especially bearing in mind that Nikonion was the only Greek centre on the western bank of the liman of the Dniester river, because of its location and size it is considered of secondary importance in the social and economic system of the Greek colonies in the Black Sea.